Proceedings of the 4th International Workshop on Java Technologies for Real-Time and Embedded Systems - JTRES '06 2006
DOI: 10.1145/1167999.1168012
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of memory allocators for real-time applications

Abstract: Real-Time applications can require dynamic storage management. However this feature has been sistematically avoided due to the general belief about the poor performance of allocation and deallocation operations in time and space. Actually, the use of Java technologies in real-time require to analyse in detail the performance of this feature due to its intensive use. In a previous paper, the authors proposed a new dynamic storage allocator that perform malloc and free operations in constant time (O(1)) with a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
0
14
0
3
Order By: Relevance
“…More recently, Masmano et al compared the first-fit, best-fit, binary-buddy [Knuth 1997], DLmalloc [Lea, D. 1996], Half-fit, and TLSF memory allocators for real-time applications [Masmano et al 2006]. Results have indicated that TLSF and Half-fit can be used by real-time applications due to stable and bounded response times.…”
Section: Time-predictable Allocatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Masmano et al compared the first-fit, best-fit, binary-buddy [Knuth 1997], DLmalloc [Lea, D. 1996], Half-fit, and TLSF memory allocators for real-time applications [Masmano et al 2006]. Results have indicated that TLSF and Half-fit can be used by real-time applications due to stable and bounded response times.…”
Section: Time-predictable Allocatorsmentioning
confidence: 99%
“…In contrast, algorithms designed to optimize AVG execution times, such as DLmalloc and binary-buddy, are not suitable for real-time applications. Half-fit achieves bounded response times wasting more memory than TLSF [Masmano et al 2006]. …”
Section: Time-predictable Allocatorsmentioning
confidence: 99%
“…Hence, these programmers do not know that plenty of heap management algorithms are available and can be used instead of the default memory allocator. Examples of memory allocators currently available are: Hoard [10], jemalloc [14], nedmalloc [15], TCMalloc [16], TSLF [17], among others. Each allocator algorithm has its specifics and several research works (e.g., [10], [17], [18]) have investigated the most used implementations.…”
Section: B User-level Memory Allocator (Uma)mentioning
confidence: 99%
“…Algorithms such as first-fit, best-fit, segregated lists and buddy systems have been widely used in various programming environments and operating systems [55,56]. Comparison between such algorithms' time and space performance can be found in [72,55,56] as well. However, their time and space overheads are still too high for a real-time system [21].…”
Section: Manual Approachmentioning
confidence: 99%